Het vak levensbeschouwing op middelbare rooms-katholieke scholen: Waar moet het aan voldoen? - van Dijk-Groeneboer, Monique (Religie & Samenleving, 2018)
In the secularised Netherlands, Roman Catholic schools are populated by a diverse population of which Catholics are only a minority. Therefore, Catholic religious education has to deal with the challenges educating religion to young people who are short of knowledge about religion and who only have superficial ideas about religion. Cognitive training is necessary to overcome this gap, but even more important religious education has to focus on the unique qualities of each pupil in the classroom, trying to enhance his and her roots, make them strong human beings to face the challenges in their full everyday life. A genuine dialogue and well-designed activating exercises is what we hope to develop to fulfil this obligation as teachers at Catholic, and all other, secondary schools.